Prescribing pattern of antibiotics in the department of pediatrics in a tertiary care medical college hospital in Northern India (Asian Journal of Medical Sciences, 2014)
Background: Systemic antibiotics account for more than one?third of all prescriptions in children; hence, antibiotic prescriptions in children are a major public health concern. Moreover, data regarding rational antibiotic use in children is very limited. Hence, it is essential that the antibiotic prescribing pattern be evaluated periodically for its rationality of use and cost. The aim of our study is to identify the prescribing pattern and to carry out direct cost analysis of antibiotic use in the patients admitted in pediatrics department of a tertiary care hospital of North India. Methods: The study was conducted for two months (June, July, 2012) in pediatric ward and ICU. The data regarding patient demographics and antibiotic use was collected daily in a structured proforma. A descriptive analysis of the data was done. Results: A total of one hundred and ninety one patients were enrolled, most of them belonging to the age group 2?14 years. Majority of them were male pediatric patients (75.9%) with mean age of 4.6 years. On an average 1.9 AMAs were prescribed per patient. The most common AMAs prescribed were cephalosporins followed by aminoglycosides. The preferred route of administration was injectable (92%). The average direct cost of treatment per patient was estimated to be Rs. 3338. The percentage of drugs prescribed by generic name was 58%. Conclusions: Male pediatric patients have better access to tertiary medical care as compared to female pediatric patients. The average number of anti?microbials prescribed is 1.9 which is not too high. Newer generation of antibiotics are more commonly prescribed leading to increased cost of therapy. This baseline study will help in formulating an antibiotic policy and standard treatment guidelines for appropriate use of antibiotics. DOI: http://dx.doi.org/10.3126/ajms.v5i4.10213 Asian Journal of Medical Sciences 2014 Vol.5(4); 69-72